The Implementation of Valsava Manuever on Pain Reduction During IV Cannulation : A literature review - pratiwi, anggi (LPPM AKPER FATMAWATI, 2023)
Intravenous cannulation is one of the most commonly performed invasive procedures in clinical practice. Inserting a cannula into a vein is a routine procedure, which in some patients may none the less cause discomfort. It can cause significant pain and also distress. Valsalva maneuver is non-invasive, non-pharmacological and effective method to reduce pain. The purpose of this literature review is to get an overview of the implementation of valsava manuever on Pain Reduction During IV Cannulation based on empirical studies in the last ten year. The method used in the search for articles is based on the period 2013-2022 through searches from databases such as Pubmed, Proquest, Ebsco, Sciencedirect, google scholar and CINAHL There were seven articles used for the review of this paper. The result indicate that valsava manuever effective in reducing the pain in patients undergoing intravenous cannulation. Valsalva maneuver can be incorporated by nurses as a measure of pain relief among patients receiving intravenous cannulation.